A Tale of Two Academic Tracks - Muhammad Asali (Institute of Labor Economics (IZA), 2018)
Given asymmetric information, this paper explores the need for non-tenure-track jobs in academia alongside the usual tenure-track positions. It also explains the coexistence of these two types of jobs in research universities as an equilibrium phenomenon. The increased effort needed to produce research, accompanied by imprecisions in the academic editorial process, explains the recent increasing trend in the share of non-tenure-track jobs in academia as well as the widening wage gap between tenure-track and non-tenure-track academics.
Keywords: J21; J11; J24; J31; J41; J44; I23; 330; efficiency wages; tenure-track; coexistence of two contracts in equilibrium